Implementasi Sistem Kendali PID pada Gimbal Kamera 2-sumbu dengan Aktuator Motor Brushless - Tri Kuntoro Priyambodo (IndoCEISS in colaboration with Universitas Gadjah Mada, Indonesia., 2017)
Unmanned Aerial Vehicle has been developed for the benefit in various fields. One of them is in the field of aerial photography. Taking pictures using unmanned aircraft, in addition to a good camera, also requires gimbal camera components as camera stability controller. Gimbal camera as stability controller helps the camera to obtain a better image orientation. Gimbal camera serves to reduce vibration and movement that would interfere with the camera when taking pictures caused by the movement of the drone itself. In an effort to get to the maximum camera stability, it is necessary a control systems. This study developed a camera gimbal control system with PID method. The controller is implemented in a microcontroller and uses a brushless motor as the actuator. The brushless motor is chosen because it has several advantages including the high-efficiency, longer lasting and have a good response. In order to facilitate the search for a constant value control, in this study is used Ziegler-Nichols tuning method. The final tuning on roll angle gives constant values Kp = 0:37, Ki = 0:01, and Kd = 0:29 with average response time = 0.8 seconds. While tuning on the pitch angle gives constant values Kp = 0:55, Ki = 0:01, and Kd = 0:29 with average response time = 0.7 seconds.